Consequences of ground water development for Cebu City - Soriano, Roberto Sison; Gupta, Ashim Das; Nielsen, Mogens Dyhr; Verma, R.D.; Bogardi, Janos J.; Keidanren (Bangkok : Asian Institute of Technology, 1985)
To investigate the consequences of groundwater development for water supply in the coastal aquifer of Cebu City, a numerical groundwater flow model developed by Boonstra and de Ridder (1981) was adopted. The model was calibrated based on available information on the Cebu City aquifer. The steady state solution was obtained to set the initial conditions by varying the hydraulic conductivity and the groundwater recharge from rainfall. The storage coefficient was the parameter used in calibrating the model for the non-steady state. Model results gave an estimate of the regional values of the calibration parameters used. The calibrated model was used to predict future water levels in the aquifer based on assumed withdrawal patterns in the study area. The related effect of such patterns on the groundwater quality were also discussed. The predictive capacity of the model could be improved by incorporation of other parameters such as the depth of the saturated thickness and other sources of recharge. It is recommended that further field investigation be done to provide useful information for a better conceptualization of the aquifer system.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1985
Keywords: Water, Underground -- Philippines -- Cebu